Usability of mobile retailing application: personalizing women’s attributes - Bujang, Azlina; Sulaiman, Sharin; Haji Bibi, Zainon; Johari, Aiza; Mohd Suki, Norbayah; Mohd Suki, Norazah (International Journal of Engineering and Technology, 2018)
Digital era has considerably changed the way of the management and execution of daily operation conducted in business. The advancement of technology and Internet has transformed the traditional marketing systems and methods where they enable retailers to stay connected to global buyers in a much faster and efficient way. This study focuses on the discovery of the women’s attributes that influence the usability of the mobile retailing application. Apart from that, a prototype of DeLemari mobile retailing application has also been developed and evaluated as it can be an innovative way of offering products and services that specifically personalising women's needs. This study was conducted using mixed method: qualitative and quantitative methods approach. Without a doubt, mobile retailing application platform has dramatically transformed the way of conducting online businesses in order to reach out to women buyers, 24 hours and seven days a week. For that reason, this study needs to be conducted to explore how personalising women’s attributes can contribute to successful mobile retailing among womenfolk, thus enhances its usability. Furthermore, the right interface of the mobile sites for retailing should be considered and customised based on these personalising factors such as personalization, connectivity, interfaces: navigation feature and design, ease of use, and reachability. Based on the result, the strengths of DeLemari are in terms of its minimal, feminine and elegant design that influenced most of the intended users.